PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII A MTs. ALKHAIRAAT BIROMARU PADA MATERI ARITMATIKA SOSIAL - Lisdayanti Sultan; Hajerina Hajerina (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The basic problem in this study is the low students learning outcomes in social arithmetic material regarding the profit, loss and percentage and discount in class VII A MTs Alkhairaat Biromaru 2017/2018 school year. There are several causes of the low students learning outcomes including teachers are still learning centers so students still tend to be passive in learning. This makes students become inactive, recultant, afraid and ashamend to ask. Therefore, to improve the learning outcomes of students of class VII A MTs Alkhairaat Biromaru and maximize learning, the researcher applied a quantum learning model, which is a learning model whose entire learning process can sharpen understanding and memory, and make learning a pleasant and useful process, so that learning becomes more motivated. The quantum learning model consists of 6 learning components, namely : 1. grow, 2. natural, 3. name, . demonstrate, 5. repeat, 6. Celebrate This research is a classroom action research using qualitative approachthat aims to improve the learning outcomes of class VII A MTs Alkhairaat Biromaru sudents. The subject of this study were all students of class VII A totaling 21 people. In the research tht has been carried out, the result of his study indicate that learning activities have been going well and have increased in each cycle. This can be seen from the percentage of completeness of classical learning. In the final test of the first cycle reached the average score of students that is 71,43% with the amount of absorption of 15 students. Then in the final test the second cycle increased to 85,71% in good qualifications. With the number of students who get individual absorption of 18 students.